Ice massage on the calf improves 4-km running time trial performance in a normothermic environment - Franco-Alvarenga, P. E.; dos Santos Cechetti, M.; Barcelos, D.; Canestri, R.; Brietzke, C.; Vinicius, I.; Goethel, M. F.; Ferreira, G. A.; Pires, F. O. (Research Quarterly for Exercise and Sport, 2023)
Purpose: Local cooling with ice massage is a practical and inexpensive technique to decrease perceptual stress and improve motor performance in hot environments. However, it is unknown whether local cooling with ice massage reduces perceptual responses to exercise and improves performance in a normothermic environment. Thus, we investigated whether ice massage on the calf muscles before a 4 km running time trial (TT4km) reduced the ratings of perceived exertion (RPE) and perceived muscle pain, thereby improving exercise performance in a normothermic environment.